THE EFFECT OF SERVICE QUALITY ON CUSTOMERS’ SATISFACTION AND WORD OF MOUTH - Sugama I P.Y.; Sukaatmadja I P.G. (Russian Journal of Agricultural and Socio-Economic Sciences, 2020)
Banking business represent the service business which its pursuant to belief, meaning that problem in service quality will determine its success. Emulation which progressively tighten within competitors makes the Bank BPD Bali Cabang Pembantu Sanur must show itself by giving best service and exceeds all its competitor. This matter conducted to create client satisfaction shown by positive word of mouth. The research target is to explain the influence of service quality to client satisfaction; influence of satisfaction on customer’s word of mouth; influence of service quality on customer’s word of mouth, and influence of service quality to word of mouth through of client satisfaction. The research conducted at Bank BPD Bali Cabang Pembantu Sanur. 100 respondents are used as sample, with questionnaire as instrument. Analysis technique used is SEM (Structural Equation Modelling) with help of the statistical program AMOS (Analysis of Moment Structure). The results indicate that there are positive and significant effect of service quality on client satisfaction, satisfaction have a positive and significant effect on customer’s word of mouth, service quality have a positive and significant effect on customer’s word of mouth, and satisfaction by full model able to mediate the effect of service quality to customer’s word of mouth. Pursuant to research result, hence it is suggested to members of management of Bank BPD Bali Cabang Pembantu Sanur to routinely pay attention to its service quality, which are measured by pursuant to reliability dimension, response, guarantee, empathy, and physical evidence, to be service quality given a company remain to be awaked which later can improve the satisfaction and intensity of customer’s word of mouth.